Vulnerable users to assess urban quality - Tiboni, Michela; Rossetti, Silvia (TeMA - Journal of Land Use, Mobility and Environment, 2012)
The main users of nowadays urban spaces are not only “standard men”, adults and healthy people like suggested by the image of the Vitruvian man, but weak users like children, the elderly and the disabled as well. As reminded by Laurìa all these people have many needs. And, as said by cardinal Tettamanzi, the rights of weak people are not weak rights. In the lasts decades European cities have been largely dominated by cars and vulnerable users have been confined in residual spaces. Thus, there is nowadays a need of a new “measure” for the urban design, to ensure an easy access and use of the of the city also for the weak users. This paper doesn’t aim at proposing planning, design and management solutions for urban spaces: many other researches have already dealt with those issues and among the most recent there are Caramona et alii (2010), Colarossi e Latini (2008), Rotondo e Selicato (2010). This paper arguments instead the need to regain the right measure while dealing with urban planning: only in this way the usability of the urban an public spaces will increase for everyone, both vulnerable users and not. The aim is to build a “friendly city”, as it has been called within the CeSCAm (research centre for friendly cities) activities. Children may represent the brick on which the urban projects have to be based: a city where children can move around without risks and fears is a city where the quality of life is high and it is a city characterized by a great attention on sustainable mobility issues, on proximity spaces, on green areas…